Acute diarrheal disease outbreak in Muzaffarpur Village, Chandauli District, Uttar Pradesh, India - Ginisha Gupta; Akhileshwar Singh; Tanzin Dikid; Ekta Saroha; Samir V Sodha (Indian Journal of Public Health, 2021)
Background: Acute diarrheal disease (ADD) outbreaks frequently occur in the Gangetic plains of Uttar Pradesh, India. In August 2017, Muzaffarpur village, Uttar Pradesh, reported an ADD outbreak. Objectives: Outbreak investigation was conducted to find out the epidemiology and to identify the risk factors. Methods: A 1:1 area-matched case–control study was conducted. Suspected ADD case was defined as ≥3 loose stools or vomiting within 24 h in a Muzaffarpur resident between August 7 and September 9, 2017. A control was defined as an absence of loose stools and vomiting in a resident between August 7 and September 9, 2017. A matched odds ratio (mOR) with 95% confidence intervals (CIs) was calculated. Drinking water was assessed to test for the presence of any contamination. Stool specimens were tested for Vibrio cholerae, and water samples were also tested for any fecal contamination and residual chlorine. Results: Among 70 cases (female = 60%; median age = 12 years, range = 3 months–70 years), two cases died and 35 cases were hospitalized. Area–A in Muzaffarpur had the highest attack rate (8%). The index case washed soiled clothes at well – A1 1 week before other cases occurred. Among 67 case–control pairs, water consumption from well–A1 (mOR: 43.00; 95% CI: 2.60–709.88) and not washing hands with soap (mOR: 2.87; 95% CI: 1.28–6.42) were associated with illness. All seven stool specimens tested negative for V. cholerae. All six water samples, including one from well–A1, tested positive for fecal contamination with <0.2 ppm of residual chlorine. Conclusion: This outbreak was associated with consumption of contaminated well water and hand hygiene. We recommended safe water provision, covering wells, handwashing with soap, access to toilets, and improved laboratory capacity for testing diarrheal pathogens.